PORTRAIT OF PAI TEACHER IN THE IMPLEMENTATION OF THE 2013 CURRICULUM TOWARDS AN INDEPENDENT LEARNING CURRICULUM AT AR-RAHMAN HIGH SCHOOL MEDAN HELVETIA - Siregar, Bahtiar; Tumiran, Tumiran; Nurrayza, Nurrayza; Putri, Vinita (Proceeding International Seminar of Islamic Studies, 2023)
The new policy initiated by Minister of Education and Culture Nadiem Makarim during his early tenure caused perceptions in all circles of society, especially in the field of education, therefore researchers wanted to raise and find out about the problem at one of the educational institutions located at Ar-Rahman High School Medan Helvetia to find out the views of PAI teachers on the concept of Independent Learning of the Minister of Education and Culture. Merdeka Belajar is the freedom of thought, which starts and ends from the teacher, he invites educational elements to participate in advancing education in Indonesia. This study aims to determine the perception and implementation of teachers about the concept of Independent Learning Minister of Education and Culture Nadiem Makarim in Islamic religious education at Ar-Rahman High School Medan Helvetia.  This research is a type of qualitative research that aims to describe the phenomenon of a condition in the field, Informal this research uses Purposive sampling techniques, and data collection techniques, namely observation, interviews and documentation. The results of this study are: 1) PAI teachers at Ar-Rahman High School Medan Helvetia, have a positive perception of the concept of Merdeka Belajar Mendikbud Nadiem Makarim which is reflected in the willingness to follow existing policies, 2) Making a Learning Implementation Plan (RPP) with the concept of Independent Learning Minister Nadiem Makarim is carried out with steps such as holding a Workshop, 3) The implementation of active learning online is carried out by multiplying interactive learning techniques  and communicative, using learning media.